2008
DOI: 10.2186/jjps.52.513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Masticatory Part and the Habitual Chewing Side by Wax Cube and Bite Force Measuring System (Dental Prescale)

Abstract: The results of this study suggested that the evaluation of the masticatory side and the use of Dental Prescale were helpful in determining the habitual chewing side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Similar to a dominant hand, humans have a habitual chewing side on which chewing is easier and show a functional difference compared with the non-habitual side [4,23]. Recently, the habitual chewing side has come to be used when evaluating masticatory performance [9,10,17].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a dominant hand, humans have a habitual chewing side on which chewing is easier and show a functional difference compared with the non-habitual side [4,23]. Recently, the habitual chewing side has come to be used when evaluating masticatory performance [9,10,17].…”
Section: Discussionmentioning
confidence: 99%
“…28 The patient bites on the 98 mm (0.1 mm) thick film for 10-20 seconds, and then the film layer is inspected under a polariscope light to obtain the relative tooth contact intensity. 29 It has been shown that the photoelastic wafer enhances posterior contact intensity and diminishes that of the anterior region. Furthermore, investigators have concluded that the photo-occlusion method consists of a complicated technique used for occlusal analysis 30 and is not highly reproducible.…”
Section: Photo-occlusion Systemmentioning
confidence: 99%
“…In one study, the habitual chewing side showed no correlation with MBF in complete denture wearers . In adults with natural dentition, it has been observed that the preferred chewing side is closely related to bite force .…”
mentioning
confidence: 96%
“…18,19 In one study, the habitual chewing side showed no correlation with MBF in complete denture wearers. 20 In adults with natural dentition, it has been observed that the preferred chewing side is closely related to bite force. 21 A study comparing bite force in patients with an implant-supported fixed prosthesis and natural dentition on the opposite side found that MBF was significantly higher on the dentate side.…”
mentioning
confidence: 99%